La utilización adecuada de los espacios deportivos de la Universidad Técnica de Cotopaxi en el año 2012 - 2013, Diseño de un centro de recreación y deportes para los estudiantes de la institución. - Arequipa Yanchapaxi, Eduardo Cristóbal (2015)
Physical activity and sports practice in general have historically been seen as an important event in the life of peoples, with periods of exaltation and regression as happened in the Middle Ages. Technological, economic, social and cultural development has had several repercussions on the amount of physical exercise and the good use of free time in the Today's man and woman, this socioeconomic aspect has direct value in the quantity and quality of the practice of physical activities and sports to which university students dedicate themselves. Over the years physical activity and recreation were carried out with various purposes, especially for the benefit of health, body development and mental, hence the enormous importance of physical and recreational activities systematically at all levels and strata of societies. With the elaboration of the design of a recreation and sports center, we have the purpose of improving sports practices with the application of a program recreation for college students, involving a wide range of activities that humans can do in their free time, involves breaking away from the everyday and routine to being an active student.